2018
DOI: 10.1039/c7sc02536j
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a “bump-and-hole” approach to allele-selective BET bromodomain inhibition

Abstract: Allele-specific chemical genetics enables selective inhibition within families of highly-conserved proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
67
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 60 publications
2
67
0
1
Order By: Relevance
“…Interestingly, the clash with Leu387 is similar to that exploited in our bump-and-hole study for the same residue (Figure 3 B). [29,30] The enhanced discrimination between BD1 and BD2 could potentially be attributed to differences in the ZA-loop of BD1s compared to BD2s. Sequence alignment of the six bromodomains revealed an additional proline (Pro397) in BD1 which could limit the ability of the BD1s to accommodate the extra linker present in macroPROTAC-1 (Supporting Information, Figure S7).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the clash with Leu387 is similar to that exploited in our bump-and-hole study for the same residue (Figure 3 B). [29,30] The enhanced discrimination between BD1 and BD2 could potentially be attributed to differences in the ZA-loop of BD1s compared to BD2s. Sequence alignment of the six bromodomains revealed an additional proline (Pro397) in BD1 which could limit the ability of the BD1s to accommodate the extra linker present in macroPROTAC-1 (Supporting Information, Figure S7).…”
Section: Methodsmentioning
confidence: 99%
“…FRAP‐Studien zeigten, dass bereits die Blockade von BRD4(1) ausreicht, um BRD4 vom Chromatin zu verdrängen. Diese spezielle Strategie kann dazu beitragen, ein tieferes Verständnis für die Bedeutung der einzelnen BET‐Bromodomänen im zellulären Kontext zu erlangen . Law et al.…”
Section: Biochemische Techniken Zur Untersuchung Von Bromodomänenunclassified
“…We used this new system to dissect individual roles of BD1 vs. BD2 in Brd4 and the other BET proteins and showed that while the BD1 is necessary and sufficient for chromatin binding, the BD2 plays a role in transcriptional regulation. 24,25 Our previous approaches for incorporation of an alkyl "bump" into the I-BET scaffold involved alkylation of a potassium enolate to afford bumped I-BET derivatives with undesired diastereoselectivity and in low yields ( Fig. 2A).…”
mentioning
confidence: 99%
“…Due to the use of potassium hexamethyldisilazide (KHMDS) for the enolization, and the need of an epimerisation step at such a late stage of the synthesis, the products are racemic and require chiral separation to isolate the eutomers. [24][25][26] Separation of the enantiomers can be costly (up to £1000 for <150 mg of racemate) and leads to loss of material during the separation.…”
mentioning
confidence: 99%
See 1 more Smart Citation